Implementation on Visualization of Some Complex Physics Problems Embodied in Difficulty with Interactive Materials for Undergraduates - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
Physical phenomena and the nature of materials require both qualitative and quantitative research to be understood thoroughly. This process often necessitates the use of complicated and expensive equipments. Also in electrical-electronics discipline, especially the nature of semiconductor materials and the behavior of them have a special place. In engineering education, it is often more important for undergraduates to understand the behavior of material and the results of that at the basic level. For this purpose it is sufficient to analyze semiconductor materials with interactive software unlike physics scholars who apply mostly physically to analyze. Understanding the physical properties of applied materials and digitalizing the characteristics of these materials by coding in programming environment maintain its importance. In this context, designing of interactive programs to analyze physical phenomena in electrical-electronics engineering without the need for licensed software has been presented. For this purpose, some semiconductor phenomena involved with electronics engineering have been selected as a pilot and web based 3D Java graphic AWT applications have been designed.
Keywords: SIMULATION; JUNCTION